Graphical model for joint segmentation and tracking of multiple dividing cells - Schiegg, Martin; Hanslovsky, Philipp; Haubold, Carsten; Köthe, Ullrich; Hufnagel, Lars; Hamprecht, Fred (Bioinformatics, 2015)
Abstract. Motivation: To gain fundamental insight into the development of embryos, biologists seek to understand the fate of each and every embryonic cell. For